Previous experiences of pregnancy and early motherhood among women living with HIV: a latent class analysis. Issue 11 (2nd November 2019) - Fortin-Hughes, Marilyn; Proulx-Boucher, Karène; Rodrigue, Carl; Otis, Joanne; Kaida, Angela; Boucoiran, Isabelle; Greene, Saara; Kennedy, Logan; Webster, Kath; Conway, Tracey; Ménard, Brigitte; Loutfy, Mona; et al.
ABSTRACT: Previous maternity experiences may influence subsequent reproductive intentions and motherhood experiences. We used latent class analysis to identify patterns of early motherhood experience reported for the most recent live birth of 905 women living with HIV enrolled in the Canadian HIV Women's Sexual and Reproductive Health Cohort Study (CHIWOS). Four indicators were used: difficulties getting pregnant, feelings when finding out pregnancy, feelings during pregnancy, and feelings during the first year postpartum. Most (70.8%) pregnancies analyzed occurred before HIV diagnosis. A four-class maternity experience model was selected: "overall positive experience" (40%); "positive experience with postpartum challenges" (23%); "overall mixed experience" (14%); and "overall negative experience" (23%). Women represented in the "overall negative experience" class were more likely to be younger at delivery, to not know the HIV status of their pregnancy partner, and to report previous pregnancy termination. Women represented in the "positive experience with postpartum challenges" class were more likely to report previous miscarriage, stillbirth or ectopic pregnancy. We found no associations between timing of HIV diagnosis (before, during or after pregnancy) and experience patterns. Recognition of the different patterns of experiences can help providers offer a more adapted approach to reproductive counseling of women with HIV.